South Africa : Reducing Financial Constraints to Emerging Enterprises - Riley, Thyra A. (2012)
South Africa's black enterprise sector is a residual employer with an important role to play in improving welfare and alleviating poverty. It is also a source of dynamic and potentially dynamic firms that create wealth and generate employment. The challenge facing South Africa is to design an institutional framework that accords black enterprises much broader access to financial services, training, and technical assistance. That framework is contained in the government's policy paper, National Strategy for the Development and Promotion of Small Business in South Africa. Details of the institutional framework to increase access to financial services by emerging enterprises are discussed here. Like South Africa, many countries in Africa, Asia, and Latin America face severe unemployment, a stagnant formal economy and a burgeoning informal economy made up of small enterprises which constitute the only means of livelihood for a substantial share of the population. South Africa's efforts to develop its formal financial sector's capacity to serve the needs of small, new businesses offers potentially interesting lessons for other countries.